Leprosy as a model to understand cancer immunosurveillance and T cell anergy. Issue 1 (22nd April 2016) - Park, Andrew J; Rendini, Tina; Martiniuk, Frank; Levis, William R
Abstract : Review on parallels that leprosy immune T cell response brings to cancer immunosurveillance, immunoediting, and immunotherapy. Abstract: Leprosy is a disease caused by Mycobacterium leprae that presents on a spectrum of both clinical manifestations and T cell response. On one end of this spectrum, tuberculoid leprosy is a well-controlled disease, characterized by a cell-mediated immunity and immunosurveillance. On the opposite end of the spectrum, lepromatous leprosy is characterized by M. leprae proliferation and T cell anergy. Similar to progressive tumor cells, M. leprae escapes immunosurveillance in more severe forms of leprosy. The mechanisms by which M. leprae is able to evade the host immune response involve many, including the alterations of lipid droplets, microRNA, and Schwann cells, and involve the regulation of immune regulators, such as the negative checkpoint regulators CTLA-4, programmed death 1, and V-domain Ig suppressor of T cell activation—important targets in today's cancer immunotherapies. The means by which tumor cells become able to escape immunosurveillance through negative checkpoint regulators are evidenced by the successes of treatments, such as nivolumab and ipilimumab. Many parallels can be drawn between the immune responses seen in leprosy and cancer. Therefore, the understanding of how M. leprae encourages immune escape during proliferative disease states has potential to add to our understanding of cancer immunotherapy.